١١٦ Academic Specialization and its relationship to job performance of The officials ofBaghdad University Presidency (Journal of the College of Education for Women, 2019)
The aims of this research is to investigate : The nature of academic specialization of the officials of Baghdad University Presidency , Level of job performance of the officials of Baghdad University Presidency through job performance appraisal form per year , Differences in the levels of job performance of the officials of Baghdad university presidency , according to the variables (sex , academic specialization , the current work , the duration between the date of graduation and the date of appointment , service duration) , The relationship of academic specialization of the officials of Baghdad university presidencywith their job performance . The researcher has followed the analytical descriptive mode to achieve the aims of this research . The population of the research includes the officials of Baghdad University Presidency having B . A degree in different specializations who are appointed as permanent cadre members , and those who have got job performance appraisal in (2009). This population consists of (290) officials ,Two resources have been used to achieve the aims : ( job information form ) and ( job performance appraisal form) . The present research results are : - That officials of Baghdad University Presidency have graduated from ( 21) different Colleges . They hold academic specializations (scientific , humanitarian). - That the job performance level is statistically evident when compared with the hypothetic medium (50) degree at the level (0,05) . - The presence of statistically evident differences in the levels of job performance on the sex , academic specialization , service duration, and no statistically evident differences in the current work, the duration between the date of graduation and the date of appointment . - There is no statistically evident relationship between the academic specialization and the job performance of Baghdad university presidency officials . According to the results and conclusions attained , the researcher has come to a number of recommendations and suggestions for research that will complement the subject of current research .